2020
DOI: 10.2147/cmar.s254485
|View full text |Cite
|
Sign up to set email alerts
|

<p>Paeonol Inhibits Cell Proliferation, Migration and Invasion and Induces Apoptosis in Hepatocellular Carcinoma by Regulating miR-21-5p/KLF6 Axis</p>

Abstract: Background Hepatocellular carcinoma (HCC) is one of the most common tumors with high mortality. MicroRNAs (miRNAs) were reported as crucial markers for the diagnosis of HCC. Paeonol exerted many pharmacological effects on tumor progression. This study aimed to elucidate the underlying molecular mechanism of paeonol in HCC progression. Methods Cell viability was determined by Cell Counting Kit-8 (CCK-8) assay. Cell apoptosis was examined by flow cytometry. The levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“… Li et al., 2020 ; Mohammed Thangameeran et al., 2020 ), and this background indicates that ferroptosis is a key process in ICH-induced neuronal injury. A previous report showed that PAN inhibited the progression of inflammation and cancer (M. Cai et al., 2020 ; Shi et al., 2020 ; J. J. Zhang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“… Li et al., 2020 ; Mohammed Thangameeran et al., 2020 ), and this background indicates that ferroptosis is a key process in ICH-induced neuronal injury. A previous report showed that PAN inhibited the progression of inflammation and cancer (M. Cai et al., 2020 ; Shi et al., 2020 ; J. J. Zhang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…Our research is the first to find that PAN alleviates ferroptosis in ICH, which supplements our knowledge of the underlying mechanism of PAN in ICH. It has been reported that HOTAIR participates in inflammation and cancers (L. Cai et al., 2020 ; Takei et al., 2020 ). In addition, it has been reported that HOTAIR is involved in ischaemic infarct ( Yang and Lu, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-146b-5p played a regulatory role in the proliferation and differentiation of human fibroblasts and chicken myoblasts [ 46 , 47 ]. MiR-21-5p is up-regulated in a variety of cancer cells such as non-small cell lung cancer, Hepatocellular carcinoma, melanoma, and colon adenocarcinoma cells, and has been shown to promote cell proliferation [ 48 , 49 , 50 , 51 ]. MiR-193-5p downregulation has significant angiogenic effect by inducing migration and proliferation in myocardial microvascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Zhou et al explored target SOX6 repressed proliferation of HCC cells by regulating miR-21-5p through an analysis of the effect of curcumin in HCC. 20 miR-195-5p/CDK1, miR-5589-3p/CCNB1 and let-7c-3p/CKS2 were screened as significant miRNA-mRNA axes, suggesting unfavorable prognosis in HCC. 21 The progression of HCC is caused by abnormalities in genes and biological signaling pathways.…”
Section: Introductionmentioning
confidence: 99%